An on-line SAX and HMM-based anomaly detection and visualization tool for early disturbance discovery in a dynamic industrial process. (August 2016) - Yiakopoulos, Christos; Gryllias, Konstantinos; Chioua, Moncef; Hollender, Martin; Antoniadis, Ioannis
Highlights: A novelty detection method for single process variable monitoring is introduced. A visualization tool for entire process monitoring based on SAX & HMM is presented. The proposed method is compared using the benchmark Tennessee Eastman process with the VizTree and the statistic models PCA and CVA. Abstract: In order to achieve an optimum and successful operation of an industrial process, it is important firstly to detect upsets, equipment malfunctions or other abnormal events as early as possible and secondly to identify and remove the cause of those events. Univariate and multivariate statistical process control methods have been widely applied in process industries for early fault detection and localization. The primary objective of the proposed research is the design of an anomaly detection and visualization tool that is able to present to the shift operator – and to the various levels of plant operation and company management – an early, global, accurate and consolidated presentation of the operation of major subgroups or of the whole plant, aided by a graphical form. Piecewise Aggregate Approximation (PAA) and Symbolic Aggregate Approximation (SAX) are considered as two of the most popular representations for time series data mining, including clustering, classification, pattern discovery and visualization in time series datasets. However SAX is preferred since it is able to transform a time series into a set of discrete symbols, e.g. into alphabet letters, being thus far more appropriate for a graphical representation of the corresponding information, especially for the shift operator. The methods are applied on individual time records of each process variable, as well as on entire groups of time records of process variables in combination with Hidden Markov Models. In this way, the proposed visualization tool is not only associated with a process defect, but it allows also identifying which specific abnormal situation occurred and if this has also occurred in the past. Case studies based on the benchmark Tennessee Eastman process demonstrate the effectiveness of the proposed approach. The results indicate that the proposed visualization tool captures meaningful information hidden in the observations and shows superior monitoring performance.